TRANEXAMIC ACID FOR THE PREVENTION AND THE TREATMENT OF PRIMARY POSTPARTUM HAEMORRHAGE : SYSTEMATIC REVIEW - Laurenso Lomi, Eldwin (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Despite the fact that the majority of fatalities occur in the former two groups, postpartum hemorrhage remains a leading cause of maternal mortality in both high-income and low- and middle-income nations. Uterine atony, lacerations, retained placenta or clots, and a lack of clotting factors are the most prevalent causes of postpartum bleeding. The principal treatments for this disease are uterine massage, oxytocin, and methylergonovine, as well as blood transfusions and cardiovascular support. Tranexamic acid, sometimes known as TXA, is an antifibrinolytic medication that is commonly used in the treatment and prevention of bleeding. TXA is used to treat a wide range of disorders, including severe menstrual bleeding, trauma, postpartum hemorrhage, traumatic brain injury, and surgical site bleeding. Despite having been used for several decades and a large body of research, TXA is still viewed with suspicion in many therapeutic settings. The study found that the difference in postpartum hemorrhage, mortality, and adverse effects between those who got tranexamic acid and those who received a placebo was not statistically significant. Nonetheless, studies demonstrate that tranexamic acid can help reduce postpartum bleeding.